Biblical exegesis without authorial intention? : interdisciplinary approaches to authorship and meaning - Breu, Clarissa, (Biblical Interpretation Series, 2019)
In Biblical Exegesis without Authorial Intention? Interdisciplinary Approaches to Authorship and Meaning , Clarissa Breu offers interdisciplinary contributions to the question of the author in biblical interpretation with a focus on "death of the author" theory. The wide range of approaches represented in the volume comprises mostly postmodern theory (e. g. Jacques Derrida, Michel Foucault, Paul de Man, Julia Kristeva and Gilles Deleuze), but also the implied author and intentio operis. Furthermore, psychology, choreography, reader-response theories and anthropological studies are reflected. Inasmuch as the contributions demonstrate that biblical studies could utilize significantly more differentiated views on the author than are predominantly presumed within the discipline, it is an invitation to question the importance and place attributed to the author.